Overview Of Blood Pressure and Pulse Rate in Workers Expose to Noise at PT. Bosowa Berlian Motor Kima Branch, Makassar - Z., Nurul Islah; Wahyu, Sri; Sodiqah, Yani; Nurhikmawati, Nurhikmawati; Ardhani, Ahmad (Faculty of Medicine, 2025)
Noise in the work environment is a significant health risk factor, especially in affecting workers blood pressure and pulse rate. According to the WHO, noise is defined as unwanted or excessive sound that can damage human health. At PT. Bosowa Berlian Motor Kima Branch, Makassar, high noise exposure has the potential to cause health problems such as hypertension and pulse rate disorders. This study aims to describe blood pressure and pulse rate in workers exposed to noise in this work environment. The research method uses a descriptive cross-sectional approach with secondary data collected in December 2024. The results showed that 51.6% of workers were exposed to noise above 85 dB, with 51.6% of respondents having above-normal blood pressure and 32.3% experiencing tachycardia. Factors such as length of service, length of employment, and smoking history also contribute to health risks. The conclusion of this study is that noise exposure has a significant impact on workers blood pressure and pulse rate, so interventions such as noise control, the use of personal protective equipment, and health programs are needed to reduce health risks and improve workers welfare.